Charting the field: a review of argument visualization research for writing, learning, and reasoning - Chang, Daniel; Lin, Michael Pin-Chuan; Hwang, Gwo-Jen (Frontiers in Education, 2025)
Many research studies imply that argument mapping can enhance writers' abilities in argumentation and critical thinking; however, we need to consolidate the available evidence as the first step to better understand the scope and coverage of these tools. Therefore, this paper adopts a scoping review methodology guided by the PRISMA-ScR framework. Through this systematic scoping approach, we aim to map the breadth of research on argument visualization and learning by identifying key themes and fields and highlighting gaps in empirical studies. By synthesizing existing evidence across disciplines and contexts, we hope that the scoping review will provide a foundation for future research directions, particularly in the areas of experimental validation and pedagogical design. This consolidation is especially timely given the rapid expansion of online and hybrid learning environments where such tools could provide crucial cognitive scaffolding.